PAIN MANAJEMENT INTERVENTIONS IN POST CAESAREAN SECTION PATIENTS : RAPID EVIDENCE REVIEW - Mamuroh, Lilis; Darmawan, Cahya Widyarahayu; Setiyani, Nofita; Zalva, Kinaya Vathia; Sukmawati, Sukmawati; Nurhakim, Furkon (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
Childbirth with ectio caesarianwill exxerience pain also has the risk of infection, bleeding anf complication of anesthesia surgery threttens the integrity of the body, such as bio psychosocial spiritual, and can cause discomfort such as pain response. Pharmacological and non pharmacological treatment is needed to reduce the intensity or scale of [ain. Pain is unpleasant feeling caused by tissue damage. Therefore pain management is needed to reduce the pain suffered by patients.. The purpose of this literature is to conduct a literature review related to non-pharmacological pain management in post-cesarean female patients. The article search used a computerized database, namely EBSCO, PubMed, and Scopus, and using the PICO approach. The initial article results obtained 3,638 articles, then filtered based on inclusion and exclusion criteria to produce 10 eligible articles. The results of the study showed that non-pharmacological pain management interventions were found, namely reflexology, use of abdominal binders, aromatherapy, massage, acupressure, kinesio taping, and Benson relaxation which can be done to reduce pain. Non-pharmacological therapy in addition to reducing pain also has a positive effect on the quality of breastfeeding, sleep quality, mood, reducing anxiety, relaxation, and quality of life. For further research, it hoped that other techniques can be conducted to reduce pain in pasca sectio caesaria